Adherence to antiretroviral therapy, stigma and behavioral risk factors in HIV-infected adolescents in Asia - Wasana Prasitsuebsai (2019)
© 2018 Informa UK Limited, trading as Taylor & Francis Group. We studied behavioral risks among HIV-infected and uninfected adolescents using an audio computer-assisted self-interview. A prospective cohort study was initiated between 2013 and 2014 in Malaysia, Thailand, and Vietnam. HIV-infected adolescents were matched to uninfected adolescents (4:1) by sex and age group (12–14 and 15–18 years). We enrolled 250 HIV-infected (48% male; median age 14.5 years; 93% perinatally infected) and 59 uninfected (51% male; median age 14.1 years) adolescents. At enrollment, HIV-infected adolescents were on antiretroviral therapy (ART) for a median (IQR) of 7.5 (4.7–10.2) years, and 14% had HIV-RNA >1000 copies/mL; 19% reported adherence <80%. Eighty-four (34%) HIV-infected and 26 (44%) uninfected adolescents reported having ever smoked cigarettes or drunk alcohol (p = 0.13); 10% of HIV-infected and 17% of uninfected adolescents reported having initiated sexual activity; 6 of the HIV-infected adolescents had HIV-RNA >1000 copies/mL. Risk behaviors were common among adolescents, with few differences between those with and without HIV.